Criminal defense in China : the politics of lawyers at work / Sida Liu, Terence C. Halliday. - Liu, Sida, 1980-; Halliday, Terence C. (Terence Charles) (Cambridge studies in law and society., 2017)
Criminal Defense in China studies empirically the everyday work and political mobilization of defense lawyers in China. It builds upon 329 interviews across China, and other social science methods, to investigate and analyze the interweaving of politics and practice in five segments of the practicing criminal defense bar in China from 2005 to 2015. This book is the first to examine everyday criminal defense work in China as a political project. The authors engage extensive scholarship on lawyers and political liberalism across the world, from seventeenth-century Europe to late twentieth-century Korea and Taiwan, drawing on theoretical propositions from this body of theory to examine the strategies and constraints of lawyer mobilization in China. The book brings a fresh perspective through its focus on everyday work and ordinary lawyering in an authoritarian context and raises searching questions about law and lawyers, politics and society, in China's uncertain future.